(untitled) (Journal of Philosophy Culture and Political Science, 2019)
Kazak Eli (Kazakh Nation) - The Renaissance of the Fatherland The article is devoted to revival of spiritual and material culture of the Kazakh people with the idea of «Atameken». The idea of «Atameken» fully disclosed in the epos «Kozy Korpesh - Bayan Sulu» and on the example of the Institute of biistva, the importance of this idea is substantiated. The information on the attempt to eradicate the idea of «Atameken» of the colonial policy of the USSR is provided. The problem of ethnodeformation of «Atameken» is forwarded. The goals and objectives of the idea of «Atameken» are given in the end of the article. Keywords: land of ancestors, country, land, state, people.